Analisis Kinerja Keuangan PT Indofarma (Persero) Tbk Tahun 2010-2019 - Lia Sari; Masnoni; Roy Saleh; Irsan; Ita Purmnama Sari (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2021)
The purpose of this study was to determine the financial performance of PT Indofarma (Persero) Tbk. 2010-2019 years. Analysis of the data used in this study is the analysis of financial ratios used to measure the company's financial performance, namely, liquidity ratios (current assets and cash ratios), solvency ratios (debt to equity ratios), profitability ratios (return on assets), and activity ratios. (working capital turnover). The sample taken from this research is the 2010-2019 financial statements. The data used is taken from the official website of the Indonesia Stock Exchange. The results of the study found that the financial performance of PT Indofarma (Persero) Tbk's current ratio and cash ratio showed that the company's financial performance in 2010-2019 was not good because the company had debt that was not covered by assets. Debt to equity ratio shows the company's financial performance is not good because the company is financed by debt. Return on assets shows the company's financial performance is not good because it has not been able to generate overall profits. Working capital turnover and total assets turnover shows that the company's financial performance is not good because the turnover of all assets is less effective.